CHARACTERIZATIONS OF SODIUM ALGINATE NANOEMULSIONS WITH EUCALYPTUS CITRIODORA ESSENTIAL OIL - Nascimento, Joice Farias do (2020)
The stability properties of nanoemulsions are influenced by emulsification conditions and the composition of formulations. Polymer nano-emulsions were prepared with the help of a mechanical homogenizer, in which five formulations of different concentrations were obtained in order to evaluate the stability with subsequent applications in controlled release systems. Viscosity, Particle Size and Encapsulation Efficiency were evaluated in order to obtain a stable emulsion. The N2 and N4 formulations, which were produced with 2:1 (N2) 1:2 (N4) oil and surfactant ratio and 1:1 (N2) 2:1 (N4) alginate and surfactant, stood out for having smaller Particle Size and more homogeneous size distribution. The N2 formulation obtained higher Encapsulation Efficiency, with a value of 68.2 ± 0.09%. It is assumed that the N2 nanoemulsion is the most favorable, because its formulation has a greater amount of surfactant making the interaction between the oil and the gum greater, thus having a better encapsulation capacity.